Tectonic keratoplasty using femtosecond laser lenticule in pediatric patients with corneal perforation secondary to blepharokeratoconjunctivitis: a case report and literature review - Pant, Om Prakash (J Int Med Res, 2019)
Blepharokeratoconjunctivitis secondary to ocular demodicosis in the pediatric population is often neglected and may result in a serious sight-threatening condition. In severe cases, it can lead to corneal perforation necessitating urgent corneal transplantation. However, the shortage and high cost of donor corneas is the foremost limitation of keratoplasty in developing countries. Small-incision lenticule extraction is an advanced flapless femtosecond laser refractive procedure in which an intrastromal corneal lenticule is detached and removed to correct myopia and myopic astigmatism. We herein describe a technique in which lenticules are used for the management of corneal perforation secondary to Demodex-induced blepharokeratoconjunctivitis. The lenticule was sutured over the site of the perforated cornea using 10-0 interrupted nylon sutures. The globe integrity was maintained with a good visual outcome. Thus, tectonic keratoplasty using small-incision lenticule extraction appears to be a safe, cost-effective, and reliable alternative method for the management of corneal perforation secondary to blepharokeratoconjunctivitis.